(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background: The subtrochanteric fractures represent 7-44% of the fractures of proximal femur caused by low energy trauma in elderly patients or high energy trauma in younger age group. Different surgical options used to treat and fix this fractures that could be Intramedullary devices like intramedullary nail or extramedullary devices like fixed angle blade plate. Objective: Comparing the result of close reduction and internal fixation with intramedullary nail to the open reduction and internal fixation with 95-angled blade plate for treatment of subtrochanteric fractures. Methods: Prospective multicenter study was done in Al-Imamein Al-kadhimein Medical City and Al-Wasity Teaching Hospital for thirty patients with close and open (Gustilo type-1) subtrochanteric femoral fractures between December-2014 and September-2016. Eighteen patients (8 closed + 10 open fractures) treated with Intramedullary nail (IMN) were compared to twelve patients (9 closed + 3 open fractures) treated with open reduction and 95-angled blade plate fixation (BP). Results: There were significant statistical differences between the two groups. The IMN group show better outcome regarding the mean union rate time (IMN were 16 weeks while in the BP were 22 weeks). Mean hospitalization stay (IMN were 82 hours while in BP were 110 hours) and rate of infection (IMN 0% while in BP were 16%), but no statistical difference regarding the mean operation time (IMN were 1.59 hour while in BP were 1.43 hour) and functional outcome (HHS in IMN were 82 while in BP were 79). Conclusion: Closed reduction and internal fixation with Intramedullary Nail is preferable (for Close and Open Gustilo’s type-1 Subtrochanteric fractures) when compared to the open reduction and Internal Fixation with 95-angled Blade Plate. Keywords:Subtrochanteric femur fractures, closed reduction intramedullary nail fixation, open reduction internal fixation, fixed angle blade plate. Citation: Joda AI, Aldookhi AA, Abd Ali AS. Intramedullary nailing versus fixed angled blade plating for treatment of subtrochanteric femoral fracture. Iraqi JMS. 2018; 16(2): 125-132. doi: 10.22578/IJMS.16.2.3